Tumor infiltrating lymphocytes in lung cancer: a new prognostic parameter - Reynders, Kobe; Ruysscher, Dirk De (Journal of Thoracic Disease, 2016)
There has been a long-lasting interest in the role of the immune system in the development, progression and prognosis of cancer. A seemingly straightforward way to investigate the role of the immune system in cancer is to look at the immune infiltration in the tumor. It is indeed known for many years that the microenvironment in the tumor contains natural killer cells, different types of lymphocytes and antigen presenting cells, all of which play a role in the tumor immune response. As early as 2002, the complex role of lymphocytes in cancer growth was becoming clear (1). Tumor lymphocytic infiltration (TLI) and macrophages may both promote or suppress tumor progression. Consequentially, it should not come as a surprise that studies that looked at tumor-infiltrating lymphocytes as a single entity found contradicting results for survival (2-10). Therefore, more biology-driven TIL subsets were studied (11-17). The infiltration in the tumor stroma of CD4+/CD8+ T-cells was the most consistently correlated with survival, with a higher ratio being related to a better survival in surgical patients.